Physical Properties of Binary Mixtures of ILs with Water and Ethanol. A Review. - Cabeza, Oscar; García-Garabal, Sandra; Segade, Luisa; Domínguez-Pérez, Montserrat; Rilo, Esther; Varela, Luis M. (IntechOpen, 2011)
None